Cerebral Venous Infarction due to Internal Jugular Vein Thrombosis: A Case Study and Review of Literature - Iroshani Kodikara; Dhanusha Gamage; Janaka Kalubowila (Case Reports in Medicine)
Cerebral venous sinus thrombosis (CVST) is an uncommon disease entity. In contrast-enhanced computed tomography (CT) or magnetic resonance venography (MRV) images of the brain, CVST usually manifests as a filling defect of the dural venous sinuses. Brain parenchymal involvement in CVST can be ranged from parenchymal oedema to haemorrhagic infarctions. Though the most frequent cause of haemorrhagic infarction in brain is CVST, other rare causes such as cerebral venous outflow obstruction due to neck vein pathology have been reported. We report a rare case of haemorrhagic brain infarctions secondary to bilateral internal jugular vein thrombosis in a 17-year-old woman, who has presented with worsening headache and seizures. She had high susceptibility of getting venous thrombosis for being a young female on oral contraceptive pills. While reporting a rare cause of cerebral haemorrhagic infarctions, this case report highlights the need for having a high degree of suspicion to diagnose CVST. Further, this case report emphasises the value of prompt and adequate imaging of neck veins if the haemorrhagic infarction presents with patent cerebral venous sinuses.